Face Recognition Attendance System with Face Rolling Motion on Android - Nguai, Seen Long; Mohamad Sukri, Khairul Amin (Applied Information Technology And Computer Science, 2023)
Face Recognition Attendance System with Face Rolling Motion on Android is a workspace attendance system for company’s employee to use on their own devices to take their attendance in anywhere. The Face Recognition Attendance System with Face Rolling Motion on Android is aimed to resolve the manual attendance taking method's delayed and inefficient process. It is also capable to minimize the workload of the Human Resource Department. Since the Covid-19 pandemic outbreak, the industries are looking for a solution to eliminate the virus spreading until now and the project is suitable for this problem. The project is integrated with the machine learning technology which is Huawei ML Kit’s Face Liveness Detection and Face Verification to achieve face recognition feature. The project is developed with Flutter framework and Dart language for targeted system which is Android. It also can achieve multiplatform development capabilities in the future. The result is expected to be used in anywhere and anytime. It also needs to let the employee to take attendance.